JOB MIX DESIGN BETON K -250 DENGAN MENGGUNAKAN KORAL LONG IRAM DAN PASIR MAHAKAM - NATA WIJAYA, AJI (KURVA S JURNAL MAHASISWA, 2014)
This paper presents the local matrial research supported by the testing lab so expect their analysis of the use of concrete quality k - 250 by using existing matrial at Borneo east. In the world of building this east at Borneo stout uses outside matrial for a good quality of concrete so that local matrial little use because the local matrial not good enough to use so I want to know and test the quality of the local matrial longiram coral and sand Mahakam in East Borneo.